Broccoli, Chinese—Brassica alboglabra L. - James M. Stephens (EDIS)
This document discusses Chinese broccoli (Brassica alboglabra L.), also known as gai lohn, kai lan, and Chinese kale. The plant resembles regular broccoli but has broader leaves and longer stems. It thrives in Florida gardens during fall and winter. Chinese broccoli should be grown like regular broccoli, with similar pest management. Harvesting involves cutting the flower stalks before the flowers open, leaving a portion of the stem attached for cooking. For current recommendations, visit the EDIS website or your local extension office. Original publication date May 1994.